Clotting factor activity in fresh frozen plasma after thawing with a new radio wave thawing device. Issue 5 (18th March 2019) - Kuta, Piotr; Melling, Nathaniel; Zimmermann, Robert; Achenbach, Susanne; Eckstein, Reinhold; Strobel, Julian
Abstract : BACKGROUND: Massive hemorrhage usually results in rapid need of blood products. Patients in need of fresh frozen plasma (FFP) might benefit from shorter thawing times using a novel radio wave device. So far, only one study on the prototype has been published. Activities of clotting factors after thawing FFP with the radio wave device and with a system using water cushions were compared. This is the first study analyzing the quality of FFP using the fully developed radio wave thawing device UFT100. STUDY DESIGN AND METHODS: Thirty FFP units were thawed with the UFT100 and the Plasmatherm machine. Various clotting factors and inhibitors were analyzed before freezing, immediately after thawing, and after a 48‐hour storage period at +4°C. RESULTS: After thawing, all factor activities were within normal ranges regardless of the thawing procedure. We observed significant differences in nearly all clotting factor activities regarding time as effector, whereas thawing with the Plasmatherm machine led to a significant decrease (>10%) only in factor V activity compared to the UFT100. CONCLUSIONS: Immediately after rapid thawing with the UFT100, all FFP units contained adequate coagulation factor activities to maintain hemostatic activity. The UFT100 does not deteriorate FFP quality compared to a conventional system. Regardless of the thawing system, the postthaw refrigerated storage caused a decrease in several clotting factors and inhibitors (factors V, VIII, and IX; von Willebrand factor activity; protein S and C activity) and a significant increase of factor XI.